La necesidad de reformar el código de trabajo con la finalidad de permitir licencia con sueldo al trabajador/a para el cuidado de familiares con discapacidades severas, o enfermedades catastróficas - Vintimilla Zambrano, Zhanina Eliza (2016)
In this paper we would like to indicate that the need to raise awareness of employers and workers is necessary and essential, and also join in the great struggle of workers to defend their constitutionally guaranteed rights . The work is part of the good life , the dignity of all people in their family and social therefore the while living in this world subsistence environment. The Constitution of the Republic as a guarantor of the rights of individuals, recognizes labor as a right and a social duty, an economic right , as we are entitled to receive compensation in the event of having a family member who suffers from a degenerative disease or catastrophic that requires our presence , being in these circumstances when we need more economic contribution . The rule seeks to establish the right of workers in the public and private sector to enjoy a paid leave if you have had a child , parent, spouse or diagnosed seriously ill or terminally ill , or suffer accident it would seriously threaten his life , in order to assist you. The emergency will be communicated to the employer within 48 hours to exercise that right , attaching a medical certificate signed by a licensed health professional stating the status of immediate family illness or serious risk to the life of the victim . We must remember that rights are not a gift for workers, and therefore should be protected by law